2020
DOI: 10.3390/ijerph17051466
|View full text |Cite
|
Sign up to set email alerts
|

Association between School Performance and Anemia in Adolescents in Mexico

Abstract: In school age children and adolescents, anemia might cause lower cognitive function and attention span, which in turn could diminish human capital accumulation. As children born in low-income households are more likely to be anemic, this may prevent many individuals from overcoming the intergenerational poverty traps. In this paper, we used data from the Mexican National Health and Nutrition Survey 2012 and focused on a sample of adolescents between 12 and 19 years of age to study the relationship between atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 23 publications
3
7
0
4
Order By: Relevance
“…And these total effects were found only in female or subpopulation aged 11 years, which meant anemia status may mainly affect the girls and children in puberty. Our ndings were similar to those of other studies in China and abroad 7,8,17,18 , and provided new evidence for the relationship between anemia and learning performance.…”
Section: Discussionsupporting
confidence: 90%
“…And these total effects were found only in female or subpopulation aged 11 years, which meant anemia status may mainly affect the girls and children in puberty. Our ndings were similar to those of other studies in China and abroad 7,8,17,18 , and provided new evidence for the relationship between anemia and learning performance.…”
Section: Discussionsupporting
confidence: 90%
“…16 If the anemia is not corrected on time, irreversible long-term complications such as bone diseases, liver and spleen enlargement, growth disorders, decreased motor activity, social inattention, and severe cognitive impairments will follow. [15][16][17][18] Although knowledge of the status of anemia in newborns is very important, global data on the prevalence of anemia do not include this age group and there are very insufficient studies of anemia in newborns. 19 Although newborn anemia can have severe effects on the health and wellbeing of newborns along their life course, it receives little attention from health-care providers and researchers in low-income countries.…”
Section: Introductionmentioning
confidence: 99%
“…Some previous studies reported hemoglobin continues to increase with age before reaching a plateau among teenagers [ 19 ], our results were consistent with these findings. With the improvement of living material level, the incidence of adolescence anemia due to iron deficiency is greatly reduced, hemoglobin showed an upward trend as the body gradually develops and matures [ 20 , 21 ]. Song W [ 22 ] reported similar results that hemoglobin peaks earlier in adolescent females than in males, periodic blood loss in females may be the cause of this result [ 23 ].…”
Section: Discussionmentioning
confidence: 99%